Role of chemerin in the control of glucose homeostasis. (5th February 2022) - Léniz, A.; González, M.; Besné, I.; Carr-Ugarte, H.; Gómez- García, I.; Portillo, M.P.
Abstract: Chemerin is an adipokine produced by the white adipose tissue and other tissues, which plays various roles in the pathogenesis of inflammatory and metabolic diseases in multiple organs. The present review aims at gathering scientific evidence reported in the last ten years, concerning the relationship of chemerin with alterations of glycaemic control, such as insulin resistance, type 2 diabetes and gestational diabetes in humans. Although the vast majority of the studies have shown a positive correlation between the chemerin level and a bad glycaemic control, a general consensus has not been reached. The reported results come from case-control and observational longitudinal studies, thereby limiting their interpretation. In fact, it cannot be stated whether insulin resistance and diabetes lead to an increase in chemerin levels or, on the contrary, if high levels of chemerin contribute to an impaired glycaemic control. Elevated levels of circulating chemerin are also associated with gestational diabetes mellitus. Chemerin gene polymorphisms could be proposed as mediators of glucose-related diseases. Nevertheless, to date very little is known about their implication in glucose metabolism. With regard to the mechanisms of action, chemerin impairs insulin cascade signaling by acting on several proteins of this cascade and by inducing inflammation.